Early therapeutic effects of an Angiopoietin-1 mimetic peptide in middle-aged rats with vascular dementia - Gao, Huanjia; Findeis, Elizabeth L.; Culmone, Lauren; Powell, Brianna; Landschoot-Ward, Julie; Zacharek, Alex; Wu, Trueman; Lu, Mei; Chopp, Michael; Venkat, Poornima (Frontiers in Aging Neuroscience, 2023)
Background: We previously found that in middle-aged rats subjected to a multiple microinfarction (MMI) model of vascular dementia (VaD), treatment with AV-001, a Tie2 receptor agonist, significantly improves cognitive outcome compared to control MMI rats. This study investigates the early therapeutic effects of AV-001 on inflammation and glymphatic function in rats subjected to VaD. Methods: Male, middle-aged Wistar rats (10-12m), subjected to MMI, were randomly assigned to MMI and MMI+AV-001 treatment groups. A sham group was included as a reference. MMI was induced by injecting 800±200, 70-100µm sized, cholesterol crystals into the internal carotid artery. AV-001 treatment (1µg/Kg, i.p.) was administered once daily starting at 24h after MMI. At 14 days after MMI, inflammatory factor expression was evaluated in cerebrospinal fluid (CSF) and brain. Immunostaining was used to evaluate white matter integrity, perivascular space (PVS) and perivascular Aquaporin-4 (AQP4) expression in the brain. To test glymphatic function, at 14d after MMI, 50µl of 1% Tetramethylrhodamine (3 kD) and FITC conjugated dextran (500 kD) at 1:1 ratio were injected into the CSF. Rats (4-6/group/time point) were sacrificed at 30mins, 3h, and 6h from the start of tracer infusion. Confocal microscopy was used to evaluate tracer intensities in brain coronal sections. Result: Treatment of MMI with AV-001 significantly improves white matter integrity in the corpus callosum at 14 days after MMI. MMI induces significant dilation of the PVS, reduces AQP4 expression and impairs glymphatic function compared to Sham rats. AV-001 treatment significantly reduces PVS, increases perivascular AQP4 expression and improves glymphatic function compared to MMI rats. MMI significantly increases, while AV-001 significantly decreases the expression of inflammatory factors (TNF-α, chemokine ligand 9) and anti-angiogenic factors (endostatin, PAI-1, P-selectin) in CSF. MMI significantly increases, while AV-001 significantly reduces brain tissue expression of endostatin, thrombin, TNF-α, PAI-1, CXCL9, and IL-6. Conclusion: AV-001 treatment of MMI significantly reduces PVS dilation and increases perivascular AQP4 expression which may contribute to improved glymphatic function compared to MMI rats. AV-001 treatment significantly reduces inflammatory factor expression in the CSF and brain which may contribute to AV-001 treatment-induced improvement in white matter integrity and cognitive function.